RNA sequencing profiling of mRNAs, long noncoding RNAs, and circular RNAs in Trigeminal Ganglion following Temporomandibular Joint inflammation - Liu, Xiaojun; Zhao, Chenchen; Han, Yupeng; Feng, Ruixia; Cui, Xiaona; Zhou, Yaoyao; Li, Zhisong; Bai, Qian (Frontiers in Cell and Developmental Biology, 2022)
Patients with temporomandibular joint disorders (TMD) have high levels of inflammatory pain-related disability, which seriously affects the physical and mental health of patients. However, effective treatment is yet to develop. Both Circular RNAs (circRNAs) and Long non-coding RNAs (lncRNAs) contribute to regulate pain conduction. In our current study, we report the expression profiles of circRNAs, lncRNAs and mRNAs in Trigeminal Ganglion (TG) associated with CFA induced TMD inflammation pain. The collected TGs from experimental (Complete Freund’s Adjuvant, CFA) and control (Saline) groups were processed for deep RNA sequencing. Overall, 1078,909,068 clean reads were obtained. A total of 15,657 novel lncRNAs were identified, where 281 lncRNAs were differentially expressed on CFA3D and 350 lncRNAs were differentially expressed on CFA 6D. Additionally, a total of 55,441 mRNAs and 27,805 circRNAs were identified, where and 3,914 mRNAs and 91 circRNAs were found differentially expressed, between CFA3D and Saline group, while 4,232 mRNAs and 98 DE circRNAs were differentially expressed between CFA6D and Saline group. Based on functional analyses, we found that most significant enriched biological processes of the upregulated mRNAs were involved in the immunity, neuron projection, inflammatory response, MAPK signaling pathway, Ras signaling pathway, Chemokine signaling pathway, and inflammatory response in TG. Further analyses of gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway suggest the involvement of dysregulated genes in the pain occurrence mechanism. Our findings provide a resource for expression patterns of gene transcript in regions related to pain. These results suggest that apoptosis and neuroinflammation are important pathogenic mechanisms underlying TMD pain. Some of the reported DEGs might be considered as promising therapeutic targets. The current research study revealed the expression profiles of circRNAs, lncRNAs, and mRNAs during TMD inflammation pain , and sheds lights on the roles of circRNAs and lncRNAs underlying the pain pathway in the trigeminal system of TMD inflammation pain.